Chapter L'eredità di Bruno Trentin per la sinistra europea - Pedretti, Ivan (Studi e saggi, 2023)
Trentin's reflections on the union of rights and the CGIL's European project still appear highly relevant today, in particular his idea of an Italian trade union belonging to the European socialist family in line with Delors' proposal for a Federation of Nation States and with the "Spinelli Group's" battle for the coordination of economic and social policies, the European Constitution and a united Europe in foreign policy and defense. Moreover, nowadays, the definition of a social project attentive to the work universe, in a system of rights recognized for all European citizens, as well as the attention to the issue of lifelong learning and active aging is equally important for trade unions and the left wing in Italy and Europe.